Electrical Treeing and Partial Discharge Characteristics of Epoxy/Silica Nanocomposite under Alternating Current - Jae-Jun Park (International Journal of Polymer Science)
The hydrophilic surface of fumed nanosilica was modified to a hydrophobic surface by treating it with a trimethyl silane coupling agent, and epoxy nanocomposites were prepared by mixing the modified nanosilica (0 phr, 1 phr, 3 phr, 5 phr, and 7 phr) in an epoxy matrix, where the unit phr means the parts per one hundred grams of epoxy base resin. To apply the nanocomposites to heavy electrical equipment, the effects of the modified nanosilica on the long-term treeing phenomena and the partial discharge (PD) resistance were studied under high voltage alternating current (HVAC) conditions. The bonding of trimethyl silane on the nanosilica surface was confirmed by the appearance of new peaks for the CH2 and CH3 groups in Fourier-transform infrared spectroscopy analysis. To observe the even dispersion of the modified nanosilica particles in the epoxy matrix, a transmission electron microscope was employed, and it was found that 1 phr of the modified nanosilica was uniformly dispersed; however, as the nanosilica content was increased, its aggregation became somewhat severe. The longest HVAC treeing breakdown time was found in an epoxy nanocomposite with 1 phr of alkyl-modified nanosilica, and the time was 17,412 min, which was 143.9 times longer than the 121 min required for a neat epoxy system. In a nanocomposite with 5 phr of modified nanosilica, PD resistance was found to be 12.5 times higher than that of the neat epoxy system.